Quantifying The Impact Of Current Crisis On The Convergence In EU And Post-Crisis Scenarios - Lucian-Liviu Albu (European Regional Science Association (ERSA), 2012)
Certainly the current crisis is affecting seriously the convergence process in EU. Starting from the spatial distribution in EU of some fundamental development indicators before the current crisis, we try to estimate the impact of the prolonged crisis. During last years, the less developed countries in EU were the most affected by crisis. Their investment power, as a main factor of improving the GDP growth rate, was primary affected. Moreover, the actual global crisis seems to provoke new changes in the economic growth mechanism. Among macroeconomic correlations, interest rate – investment – growth rate has a fundamental role. In the general process of economic development and in the context of convergence in EU for the post-crisis period, perhaps this relationship will become more studied by economists and policy makers. As empirical starting point, based on data for last years, we are using a 3D representation and its attached so-called geodesic map or contour plot for the correlation interest rate – investment ratio in GDP – annual GDP growth rate, for all 27 members of EU. On this map, as a general rule, we can see that GDP growth rate is higher for smaller values of interest rate and respectively for higher values of investment. Contrary, smaller growth rate corresponds to higher values of interest rate and respectively to smaller values of investment rate. Based on statistical data for last period, we try to build a set of partial models in order to investigate the growth mechanism under the impact of interest rate and respectively of ratio between investment and GDP, in case of EU members and in the same time to verify some hypotheses often used in standard economic literature. By applying such simple models derived from standard ones, in our experiment, we estimated their parameters in case of EU countries. The main two partial models are referring to the impact of investment on GDP growth rate and respectively to the relation between interest rate and investment ratio. Moreover, an equation related to the inflation dynamics was taken into account. Finally, the derived global model demonstrates complex dynamics, moreover supplying solution to estimate the so-called natural rate of interest and other key-parameters for macroeconomic decisions.
Keywords: C31; C53; E22; E27; E43; O11; O47; O52; 330; convergence; spatial distribution; investment ratio; growth rate; interest rate; depreciation rate; contour plot